The Impact of Hybrid Work Flexibility on Team Performance: The Mediating Role of Work–Life Balance and the Moderating Role of Digital Communication Quality - Ishtiaq Ahmad (Journal of Advanced Research in Social Sciences and Humanities, 2026)
Aim: The purpose of this study was to examine the impact of hybrid work flexibility on team performance, with work life balance as a mediating variable and digital communication as a moderating variable. The research aimed to provide empirical evidence on how structural flexibility, psychological balance, and technological communication collectively influence team outcomes in hybrid work environments.Methodology: A quantitative, cross-sectional design was employed, and data were collected from 275 employees working in hybrid settings across various organizations in Spain. Standardized scales were adopted from previous research to measure hybrid work flexibility, work life balance, digital communication, and team performance. Data were analyzed using ADANCO 2.3, which facilitated the assessment of measurement and structural models through structural equation modeling.Findings: The results indicated that hybrid work flexibility significantly enhances team performance both directly and indirectly through the mediating role of work life balance. Furthermore, digital communication was found to significantly moderate the relationship between work life balance and team performance, strengthening the positive association between them.Implications/Novel Contribution: This study integrates Self-Determination Theory, Conservation of Resources Theory, and Media Richness Theory to develop a holistic model explaining team performance in hybrid contexts. The findings offer both theoretical advancement and practical guidance for organizations designing flexible, balanced, and digitally supported hybrid work systems.